Reaksi Pasar atas Pengumuman Penurunan Bank Indonesia 7-Day Reverse Repo Rate - Sayudha, Anak Agung Gede Rama; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2021)
The purpose of this study is to investigate the reaction of the Indonesian capital market to the announcement of a reduction in the Bank Indonesia 7-Day Reverse Repo Rate on the property and banking sectors. This study employs an event study with a seven-day observation period. The sampling technique used was the purposive sampling technique. The sample size for the banking sector was 32 companies, and the sample size for the property sector was 30 companies. Anomaly returns were used to gauge market reaction. The researchers used the paired samples t-test and the Wilcoxon signed rank test to analyze the data. The results for both sectors revealed that no market reaction was detected as a result of the announcement. This may be caused by investors thought that the announcement can’t affect the company's performance in short term and also considering the other sentiments. Keywords: BI 7-Day Reverse Repo Rate; Event Study; Abnormal Return; Market Reaction.